Translating Observations From Leishmanization Into Non-Living Vaccines: The Potential of Dendritic Cell-Based Vaccination Strategies Against Leishmania - Seyed, Negar; Peters, Nathan C.; Rafati, Sima (Frontiers in Immunology, 2018)
Leishmaniasis is a health-threatening vector-borne disease in almost 90 different countries. While a prophylactic human vaccine is not yet available, the fact that recovery from leishmaniasis establishes lifelong immunity against secondary infection suggests that a vaccine is attainable. In the past, deliberate infection with virulent parasites, termed Leishmanization, was used as a live-vaccine against cutaneous leishmaniasis and effectively protected against vector-transmitted disease in endemic areas. However, the practice was discontinued due to major complications including non-healing skin lesions, exacerbation of skin diseases, and the potential impact of immunosuppression. Instead, tremendous effort has been made to develop killed, live attenuated and nonliving subunit formulations. Many of these formulations produce promising experimental results but have failed in field trials or against experimental challenge with infected sand flies. Recently, experimental models of leishmanization have unraveled the critical role of parasite persistence in maintaining the circulating CD4+ effector T cells responsible for mitigating the inflammatory response early after sand fly challenge and mediating protective immunity. Here, we put forward the notion that for effective vaccine design (especially non-living vaccines), the role of antigen persistence and pre-existing effector CD4+ T cells should be taken into consideration. We propose that dendritic cell (DC) based vaccination strategies warrant greater attention because of their potential to act as long-term antigen depots, thereby emulating this critical requirement of naturally acquired protective immunity against infected sand fly challenge.